Sistem Pendukung Keputusan Berdasarkan Profil Keuangan Pribadi di Aplikasi SiKencur - Andy Haryoko (JURIKOM (Jurnal Riset Komputer), 2026)
Many individuals struggle to manage personal finances due to a lack of tools that provide advice tailored to their actual spending habits. This study develops and evaluates a Decision Support System (DSS) module within a mobile personal finance application called SiKencur. The system classifies users into four financial behavior profiles based on three transaction indicators computed over a six-month window. Testing with 30 users over four weeks yielded a classification accuracy of 82.6%, a usability score of 78.4 out of 100 (“Good” category), and a user satisfaction rating of 4.2 out of 5. The system's key advantage is the integration of personalized financial guidance directly within a single platform a capability not found in comparable applications.